2005
DOI: 10.1554/05-273.1
|View full text |Cite
|
Sign up to set email alerts
|

The Signature of Positive Selection on Standing Genetic Variation

Abstract: Considerable interest is focused on the use of polymorphism data to identify regions of the genome that underlie recent adaptations. These searches are guided by a simple model of positive selection, in which a mutation is favored as soon as it arises. This assumption may not be realistic, as environmental changes and range expansions may lead previously neutral or deleterious alleles to become beneficial. We examine what effect this mode of selection has on patterns of variation at linked neutral sites by imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
555
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 506 publications
(588 citation statements)
references
References 55 publications
31
555
2
Order By: Relevance
“…16,52,53 However, our simulations have also demonstrated that even very small levels of population substructure (F ST ¼ 0.01) can result in a negative skew in the distribution of Fay and Wu's H values, such that we can no longer reject neutrality. Therefore, population structure could be an alternative explanation for the observed significant H values in the current study and in the study of Zhou et al, 10 which is consistent with results of simulations by Wakeley and Aliacar, 54 and Przeworski 42 showing the effects of migration on Fay and Wu's H statistic. Our results suggest that one must consider demographic history, including population expansion and substructure, when testing for signatures of natural selection.…”
Section: Evolutionary Inferences and Tests Of Selectionsupporting
confidence: 92%
See 3 more Smart Citations
“…16,52,53 However, our simulations have also demonstrated that even very small levels of population substructure (F ST ¼ 0.01) can result in a negative skew in the distribution of Fay and Wu's H values, such that we can no longer reject neutrality. Therefore, population structure could be an alternative explanation for the observed significant H values in the current study and in the study of Zhou et al, 10 which is consistent with results of simulations by Wakeley and Aliacar, 54 and Przeworski 42 showing the effects of migration on Fay and Wu's H statistic. Our results suggest that one must consider demographic history, including population expansion and substructure, when testing for signatures of natural selection.…”
Section: Evolutionary Inferences and Tests Of Selectionsupporting
confidence: 92%
“…Our simulations show that population structure skews the distribution of H towards negative values (although the mean value of H remains nearly the same), and this effect is more accentuated as F ST increases (ie number of migrants decreases), in agreement with Przeworski. 42 The observed F ST for the two European groups considered in this study (North European and Russian) is 0.07 (although not significantly different from zero) and is 0.024 for the two East African groups (Hadza and Maasai). When we consider an F ST value as low as 0.01, the 95% confidence interval for H in the Europeans was (À5.90, 3.57), and for East Africans was (À6.23, 4.22) for the observed level of recombination in these populations ( Table 1).…”
Section: Tests Of Neutralitymentioning
confidence: 47%
See 2 more Smart Citations
“…22 In addition, several studies have shown that some demographic scenarios can also cause negative skews in Fay and Wu's H. 42,43 To distinguish between these two possible causes of the pattern, it is useful to consider the pattern of polymorphism in the Memphis genomic region in a wider variety of human populations. Examination of HapMap (phase 3) SNP data from our resequenced region shows five overlapping SNPs that have been genotyped in 10 world populations (excluding the Japanese), including three where the derived allele is at high frequency in our sample (Supplementary Table S2).…”
Section: Discussionmentioning
confidence: 99%